2017
DOI: 10.1098/rsta.2016.0407
|View full text |Cite
|
Sign up to set email alerts
|

Alloy and composition dependence of hydrogen embrittlement susceptibility in high-strength steel fasteners

Abstract: High-strength steel fasteners characterized by tensile strengths above 1100 MPa are often used in critical applications where a failure can have catastrophic consequences. Preventing hydrogen embrittlement (HE) failure is a fundamental concern implicating the entire fastener supply chain. Research is typically conducted under idealized conditions that cannot be translated into know-how prescribed in fastener industry standards and practices. Additionally, inconsistencies and even contradictions in fastener ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…Susceptibility of steels to HE increases with an increase in material strength. This relationship was extensively studied evidencing that material conditions such as strength and/or hardness are primary conditions defining the susceptibility of steels to HE [11][12][13]. The results, as presented in Figure 4, confirm the statement showing a certain tendency between UTS, YS, and HSP of the studied steel grades.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Susceptibility of steels to HE increases with an increase in material strength. This relationship was extensively studied evidencing that material conditions such as strength and/or hardness are primary conditions defining the susceptibility of steels to HE [11][12][13]. The results, as presented in Figure 4, confirm the statement showing a certain tendency between UTS, YS, and HSP of the studied steel grades.…”
Section: Discussionsupporting
confidence: 74%
“…The linear regression modeling reveals a comparable HSP prediction quality at YS and UTS data for the studied steels, caused apparently by its high cross correlation rate, as shown in Figure 5. Brahimi et al [11] showed the embrittlement ratio decreasing smoothly with an increase in the hardness of individual high-strength steel grades. However, different alloys can have different hydrogen sensitivities despite the similar properties of hardness/strength that complicate the accurate prediction of changes in the steel properties in the presence of hydrogen [11,13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Effect of yield strength Among the parameters that determine the susceptibility to hydrogen embrittlement, the yield strength has been identified as having a significant effect with high strength metals most susceptible irrespective of composition or structure. For example, data presented by Brahimi et al (2017) suggests that for a given set of hydrogen charging conditions, the HEE index reduces from 0.5 for a steel with a Rockwell hardness 40 HRC to a HEE of less than 0.25 for a 52 HRC steel. We now investigate the effect of the yield strength on the tensile fracture strength using the model developed here.…”
Section: 2mentioning
confidence: 99%